2013
DOI: 10.1002/cam4.162
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of lung cancer using exhaled breath

Abstract: Early detection of lung cancer is a key factor for increasing the survival rates of lung cancer patients. The analysis of exhaled breath is promising as a noninvasive diagnostic tool for diagnosis of lung cancer. We demonstrate the quantitative analysis of carbonyl volatile organic compounds (VOCs) and identification of lung cancer VOC markers in exhaled breath using unique silicon microreactor technology. The microreactor consists of thousands of micropillars coated with an ammonium aminooxy salt for capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 38 publications
4
112
0
1
Order By: Relevance
“…Additional advantages of the current study include benchmarking of the simpler models with established statistical / machine-learning methods and optimization of cut-points for both individual VOCs and the number of elevated VOCs for determining whether a patient has lung cancer. It should also be noted that the carbonyl VOCs were equally effective in separating lung cancer cases from both smoking and non-smoking controls, in agreement with what we previously observed [24][25]. A limitation of the current work is that we selected the six VOCs for our simple model based on the best performing classifiers in the test data.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Additional advantages of the current study include benchmarking of the simpler models with established statistical / machine-learning methods and optimization of cut-points for both individual VOCs and the number of elevated VOCs for determining whether a patient has lung cancer. It should also be noted that the carbonyl VOCs were equally effective in separating lung cancer cases from both smoking and non-smoking controls, in agreement with what we previously observed [24][25]. A limitation of the current work is that we selected the six VOCs for our simple model based on the best performing classifiers in the test data.…”
Section: Discussionsupporting
confidence: 81%
“…Our previous work identified four lung cancer markers C 4 H 8 O, 4-HHE, C 4 H 8 O 2 , and C 2 H 4 O 2 [24] and a diagnostic method based on counting the number of elevated these four markers was developed [25]. In this study, two additional markers 4-HNE and C 5 H 10 O were identified by the statistical classification models.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The concentration of 2-butanone in exhaled breath of patients (n=51) with stages II though IV NSCLC was significantly higher than in exhaled breath of patients with stage I (n=34). The carbonyl and volatile organic compounds profile in exhaled breath determined using this new silicon microreactor technology provides for the noninvasive detection of lung cancer (8,9). Exhaled breath analysis in lung cancer patients reaches in small to midsized discovery trials sensitivities and specificities up to ≥90%.…”
Section: Role Of Biomarkersmentioning
confidence: 99%
“…29,[30][31] For example, the detection of 4-hydroxyhexenal (4HHE) and 4-hydroxy-2-nonenal (HNE) in expired breath has been correlated with lung cancer. 32,33 Lipoperoxidative production of reactive aldehyde species, such as malondialdehyde (MDA), HNE, 4-hydroxy-2-hexenal (HHE), and acrolein, appears to be the source of many of the α,β-unsaturated carbonyl compound markers associated with disease.…”
mentioning
confidence: 99%